Pd-Phosphinesulfonate bravely battles the ``vinyl halide insertion copolymerization'' barricade - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Chikkali, Samir H. (Journal of Polymer Science Part A-Polymer Chemistry, 2014)
This overview provides insights into the current state-of-the-art solutions to insertion copolymerization of functional olefinic monomers. The challenges in insertion copolymerization of functional olefinic monomers, with a special emphasis on vinyl halides, are highlighted. The crucial design of the Pd-phosphinesulfonate [Pd(PO)] enables up to 3.6 mol % incorporation of vinyl fluoride (VF) in an ethylene-VF copolymerization reaction. In a significant development, insertion copolymerization of industrially relevant functional olefin, that is, vinyl chloride (VC), was unambiguously ascertained, and a detectable amount of VC (0.4 mol %) was incorporated (at the chain end). In a detailed investigation, the in situ existence of (PO)PdH species during the polymerization was revealed, and it was demonstrated that these are indeed responsible for VC incorporation. (c) 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1-6
Keywords: functional olefin; insertion copolymerization; palladium catalyst; phosphinesulfonate; vinyl chloride

Palladium-catalyzed insertion of ethylene and 1,1-disubstituted difunctional olefins: an experimental and computational study - Gaikwad, Shahaji R.; Patel, Ketan; Deshmukh, Satej S.; Mote, Nilesh R.; Birajdar, Rajkumar S.; Pandole, Satish P.; Chugh, Jeetender; Chikkali, Samir H. (ChemPlusChem, 2020)
Insertion or coordination copolymerization of ethylene with di-substituted olefins is challenging and the choice of di-substituted mono-functional olefin versus di-substituted di-functional olefin (DDO) appears to be decisive. Here we show that DDO-inserted species are amenable to ethylene insertion and polymerization. DDOs such as 2-acetamidoacrylic acid (AAA), methyl 2-acetamidoacrylate (MAAA), and ethyl 2-cyanoacrylate (ECA) were treated with palladium complex [P perpendicular to OPdMe(L)] (P perpendicular to O=kappa(2)-P,O-Ar2PC6H4SO2O with Ar=2-MeOC6H4; L=C2H6OS) and the existence of respective insertion intermediates in moderate yield (up to 37 %) was established. These intermediates were exposed to ethylene and corresponding ethylene-inserted products were isolated and characterized. A careful comparison with three model compounds confirmed ethylene insertion and polymerization. Thus, the combined experimental and computational investigations show that DDO-inserted species can undergo ethylene insertion and polymerization.
Keywords: Homogeneous catalysis; insertion copolymerization; Olefins; Palladium; Polyethylene

Pd-iminocarboxylate complexes and their behavior in ethylene polymerization - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Gonnade, Rajesh G.; Pandole, Satish P.; Chikkali, Samir H. (Chemistry-An Asian Journal, 2020)
Designing co-catalyst-free late transition metal complexes for ethylene polymerization is a challenging task at the interface of organometallic and polymer chemistry. Herein, a set of new, co-catalyst-free, single-component catalytic systems for ethylene polymerization have been unraveled. Treatment of anthranilic acid with various aldehydes produced four iminocarboxylate ligands (L1-L4) in very good to excellent yield (75-92 %). The existence of 2-((2-methoxybenzylidene)amino) benzoic acid (L1) has been unambiguously demonstrated using NMR spectroscopy, MS and single-crystal X-ray diffraction. A neutral Pd-iminocarboxylate complex [N OPdMe(L1)] (N O=kappa(2)-N,O-ArCHNC6H4CO2 with Ar=2-MeOC6H4) C1 was prepared by treating stoichiometric amount of L1.Na with palladium precursor. The identity of C1 was confirmed by 1-2D NMR spectroscopy and single-crystal X-ray diffraction studies. Along the same lines, palladium complexes C2-C4 were prepared from ligands L2-L4 respectively. In-situ high-pressure NMR investigations revealed that these Pd complexes are amenable to ethylene insertion and undergo facile beta-H elimination to produce propylene. These palladium complexes were then evaluated in ethylene polymerization reaction and various reaction parameters were screened. When C1-C4 were exposed to ethylene pressures of 10-50 bar, formation of low-molecular-weight polyethylene was observed.
Keywords: imine; Imine-carboxylate; Insertion polymerization; Pd complexes; Polyethylene